Implementation Support Mission - Aide Memoire September 2022 - Accelerating Impacts of CGIAR Climate Research for Africa (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
From September 20-22, 2022, the World Bank and the International Center for Tropical Agriculture (CIAT) jointly undertook an Implementation Support Mission (ISM)1 for the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) (P173398) in Washington, DC and New York, NY. This supervision mission was planned around the AICCRA team’s participation in Climate Week NYC and previous plans to travel to New York.